1999
DOI: 10.1007/s004310051171
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineralisation in ex-preterm infants aged 8 years

Abstract: Ex preterm infants have significant reduction in bone mineral mass commensurate with their reduced growth and reduced bone mineral density in their hips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 23 publications
4
42
0
6
Order By: Relevance
“…Unfortunately, bone mineralization is one of the major challenges of neonatal management in low (LBW) and very low birth weight (VLBW) infants, and osteopenia is recognized with increasing frequency (2 -4). Despite the likelihood of a spontaneous resolution of the osteopenia at the appendicular (5,6) as well as at the axial skeleton (7,8), several studies in former preterm infants have demonstrated persisting lower bone mineral content (BMC) (9,10), particularly at the hip (11).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, bone mineralization is one of the major challenges of neonatal management in low (LBW) and very low birth weight (VLBW) infants, and osteopenia is recognized with increasing frequency (2 -4). Despite the likelihood of a spontaneous resolution of the osteopenia at the appendicular (5,6) as well as at the axial skeleton (7,8), several studies in former preterm infants have demonstrated persisting lower bone mineral content (BMC) (9,10), particularly at the hip (11).…”
Section: Introductionmentioning
confidence: 99%
“…Prematurity, irrespective of birth weight, was found to be associated with lower BMD in infancy and early childhood (1,(6)(7)(8)(9). In contrast, other studies in young children could not show differences in BMD due to prematurity (2,10).…”
Section: Introductionmentioning
confidence: 75%
“…Total body BMC and cortical area of the distal tibia have been reported to be lower in ex-preterm preschool children, even after adjusting for current body weight [19] . Lower bone mineral content and density has also been found in school age children born preterm [20,21] . Expreterm children have been shown to have increased urinary calcium excretion at age 8 years associated with a reduction in height and hip bone mineral density [22] .…”
Section: Osteopaenia Of Prematuritymentioning
confidence: 99%
“…Neonatal osteopathy might also adversely affect linear growth. Studies have shown that former preterm infants tend to be shorter and lighter than their term counterparts [16,17] and high neonatal alkaline phosphatase (ALP) has been significantly associated with short stature at 18 months and 10 years of age [17,18] . Total body BMC and cortical area of the distal tibia have been reported to be lower in ex-preterm preschool children, even after adjusting for current body weight [19] .…”
Section: Osteopaenia Of Prematuritymentioning
confidence: 99%